Enhancement of Optical Absorption and Bandgap Decrease of PVDF/Curcuma Longa Linn Composites: UV-Vis Technique - Falcão, E.A.; Silva, T. S.; Rodrigues, E.S.S.; Martelli, S.M. (Journal of Composites and Biodegradable Polymers, 2025)
In the present work, the polyvinylidene fluoride (PVDF) and PVDF/Curcuma longa Linn (PVDF/CLL) were prepared in five different concentrations. The FT-IR technique was used to analyze the incorporation of CLL in the PVDF matrix. The CLL introduction in the PVDF matrix increases de relative percentage of phase. The optical properties of PVDF/CLL were studied using UV-Vis spectroscopy. The incorporation of CLL into the PVDF matrix changes the optical absorption in the UV-Vis region and shifts the optical absorption edge to higher wavelengths. The optical transmittance of pure PVDF exceeds 70% from 270 nm to 1400 nm. The addition of 5% CLL reduces optical transmittance by 50%, and at concentrations above 20%, the reduction approaches 100%. The extinction coefficient of PVDF/CLL 10% presents two peaks, one at 234 nm and the other at 421 nm. However, higher concentrations of CLL change the first peak from 234 nm to 247 nm. The skin depth decreases with increasing photon energy. The CLL addition in the PVDF matrix shifts the indirect and direct optical bandgaps towards lower energies. The observed decrease in the bandgap is consistent with the optical absorption edge results. Finally, these results show that PVDF/CLL composites are potential candidates for optical and photonic applications.